The Future of Regulatory T Cell Therapy: Promises and Challenges of Implementing CAR Technology - Mohseni, Yasmin R.; Tung, Sim L.; Dudreuilh, Caroline; Lechler, Robert I.; Fruhwirth, Gilbert O.; Lombardi, Giovanna (Frontiers in Immunology, 2020)
Cell therapy with polyclonal regulatory T cells (Tregs) has been translated into the clinic and is currently being tested in transplant recipients and patients suffering from autoimmune diseases. Moreover, building on animal models, it has been widely reported that antigen-specific Tregs are functionally superior to polyclonal Tregs. Among various options to confer target specificity to Tregs, genetic engineering is a particularly timely one as has been demonstrated in the treatment of haematological malignancies where it is in routine clinical use. Genetic engineering can be exploited to express chimeric antigen receptors (CAR) in Tregs, and this has been successfully demonstrated to be robust in preclinical studies across various animal disease models. However, there are several caveats and a number of strategies need to be considered to further improve on targeting, efficacy and to understand the in vivo distribution and fate of CAR-Tregs. Here, we review the differing approaches to confer antigen specificity to Tregs with emphasis on CAR-Tregs. This includes an overview and discussion of the various approaches to improve CAR-Treg specificity and therapeutic efficacy as well as addressing potential safety concerns. We also discuss different imaging approaches to understand the in vivo biodistribution of administered Tregs. Preclinical research as well as suitability for clinical translations are discussed.